Analysis of The Effect of Coal Prices And Macroeconomic Factors on The Energy Sector Index In Indonesia - Kurniawan Rois, Misbakhuddin; Esti Riwayati, Hedwigis (Management Research Studies Journal, 2024)
This study aims to analyze the impact of external company factors, in the form of macroeconomic conditions on the energy sector index for the 2021-2023 period. The macro conditions studied are coal prices, the rupiah exchange rate against the US dollar, and inflation. The research was conducted with descriptive statistical analysis and multiple linear regression analysis with data processing using Eviews 12 data analysis. The results of this study indicate that coal prices partially have a positive significant effect on the energy sector index. while the rupiah exchange rate against the US dollar has a negative significant effect on the energy sector index. In contrast, inflation partially has no significant effect on the energy sector index during the research period.